If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3y + 1) = 7(51 + -35y) Reorder the terms: 3(1 + 3y) = 7(51 + -35y) (1 * 3 + 3y * 3) = 7(51 + -35y) (3 + 9y) = 7(51 + -35y) 3 + 9y = (51 * 7 + -35y * 7) 3 + 9y = (357 + -245y) Solving 3 + 9y = 357 + -245y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '245y' to each side of the equation. 3 + 9y + 245y = 357 + -245y + 245y Combine like terms: 9y + 245y = 254y 3 + 254y = 357 + -245y + 245y Combine like terms: -245y + 245y = 0 3 + 254y = 357 + 0 3 + 254y = 357 Add '-3' to each side of the equation. 3 + -3 + 254y = 357 + -3 Combine like terms: 3 + -3 = 0 0 + 254y = 357 + -3 254y = 357 + -3 Combine like terms: 357 + -3 = 354 254y = 354 Divide each side by '254'. y = 1.393700787 Simplifying y = 1.393700787
| 10+7x=29+14x | | 3(x+4)=5x-10 | | 8y^2=-9y+4 | | 10x-7=29-14x | | 81t^2+144t+64= | | 10-7x=29-14xr | | 3y-1+y+47=7y+50-5y | | 7x-11=2x+14 | | 17x+19y=-23 | | 19x+17y=-23 | | -17-10=7x+17 | | 7x-22=41 | | 5*12+10=4*12+p | | 5*-12+10=4*-12+p | | 5-12+10=4*-12+p | | 83=32x+10 | | 18-12+2+1= | | 60-4x=32x+16 | | 8x+4=6x+10 | | -19.48+x=28.03 | | 3x+8=-8-7x | | 10-3h=25 | | y=-4x+0 | | 5t+1=11 | | 82-5x=22x+16 | | 4x-9=175 | | 11-7x=19-14x | | 6m+11=137 | | 9y-47=43 | | 2y=36 | | b+5=59 | | 9b+24=150 |